2017
DOI: 10.1038/s41598-017-04317-0
|View full text |Cite
|
Sign up to set email alerts
|

Focal Adhesion Kinase Regulates Hepatic Stellate Cell Activation and Liver Fibrosis

Abstract: Understanding the underlying molecular mechanisms of liver fibrosis is important to develop effective therapy. Herein, we show that focal-adhesion-kinse (FAK) plays a key role in promoting hepatic stellate cells (HSCs) activation in vitro and liver fibrosis progression in vivo. FAK activation is associated with increased expression of α-smooth muscle actin (α-SMA) and collagen in fibrotic live tissues. Transforming growth factor beta-1 (TGF-β1) induces FAK activation in a time and dose dependent manner. FAK ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 69 publications
6
72
0
Order By: Relevance
“…GSEA in samples with low MPI , regardless of level of fibrosis, revealed cell and focal adhesion clusters to be consistently ranked first among the gene sets significantly enriched in these samples across data sets (Fig. C; Supporting Table ), a finding consistent with deranged cell adhesion as a hallmark of liver fibrosis . These data demonstrate an inverse correlation between MPI gene expression and fibrosis in adult human liver disease.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…GSEA in samples with low MPI , regardless of level of fibrosis, revealed cell and focal adhesion clusters to be consistently ranked first among the gene sets significantly enriched in these samples across data sets (Fig. C; Supporting Table ), a finding consistent with deranged cell adhesion as a hallmark of liver fibrosis . These data demonstrate an inverse correlation between MPI gene expression and fibrosis in adult human liver disease.…”
Section: Resultssupporting
confidence: 53%
“…1C; Supporting Table S3), a finding consistent with deranged cell adhesion as a hallmark of liver fibrosis. (22) These data demonstrate an inverse correlation between MPI gene expression and fibrosis in adult human liver disease.…”
Section: Mpi Expression Is Inversely Correlated With Advanced Fibrosimentioning
confidence: 74%
“…Crosstalk has been reported between the TGFb signaling pathway and the following pathways: MAPK, TNF, and FoxO (51)(52)(53). Associations of TGFb with hypertrophic cardiomyopathy, dilated cardiomyopathy, proteoglycans in cancer, focal adhesion, HIF1 signaling pathway, and Rap1 signaling have also been reported (54)(55)(56)(57)(58)(59). Therefore, the results of pathway analysis of TGFb targets are appropriate, as these are similar to previous reports.…”
Section: Discussionsupporting
confidence: 72%
“…Phosphorylation and the activity of FAK were up‐regulated in scleroderma dermal fibroblasts and fibroblasts of lung fibrosis patients . It has been shown that at the downstream of platelet‐derived growth factor and TGFβ receptors, FAK transmits signals to Akt, ERK, and p38 mitogen‐activated protein kinase (MAPK) pathways that contribute to HSC activation and liver fibrosis . However, it is unknown whether FAK in return modulates TGFβ receptors.…”
mentioning
confidence: 99%